Development and evaluation of the SPeeding Research-tested INTerventions (SPRINT) training program. Issue 6 (22nd July 2019) - Gaysynsky, Anna; Vinson, Cynthia A; Oh, April
Abstract : The education and counseling intervention performed by the nurse for obese and overweight women has a positive effect on healthy lifestyle behaviors and body mass index. Abstract: The National Cancer Institute established a dissemination and implementation accelerator program called SPeeding Research-tested INTerventions (SPRINT) to improve the uptake of evidence-based interventions. The purpose of this study was to describe the origin, structure, and goals of the SPRINT program, and present evaluation results from the first two cohorts of the program. Qualitative (focus group) and quantitative (survey) data collected from participants were used to evaluate the course and inform program improvement efforts. The majority of the participants (over 90% in both cohorts) rated the course highly, and over 80% would recommend the course to other researchers. Most participants indicated knowing relatively little about business model concepts before SPRINT, but after SPRINT, nearly all respondents felt that they had at least "some" knowledge of each business model component. Participants also indicated that they learned about the product–market fit of their intervention and gained insights from customer discovery interviews that would enable them to make their intervention more "stakeholder focused". Participants also indicated that they plan to use the knowledge and skills they gained during the SPRINT program in their future work. Feedback from participants was used by the management team to implement various program improvements to better serve the next cohort of participants. While behavioral researchers face significant barriers to commercializing their interventions, they recognize the importance of translating their research into practice. Training researchers to consider scale-up, implementation, and commercialization from the outset can help reduce the number of proven interventions that are never used in practice.